2010
DOI: 10.3109/07420521003663785
|View full text |Cite
|
Sign up to set email alerts
|

3111T/C CLOCKGENE POLYMORPHISM IS NOT ASSOCIATED WITH SLEEP DISTURBANCES IN UNTREATED DEPRESSED PATIENTS

Abstract: Sleep patterns, frequently altered in depression, have been hypothesized to be under genetic control. The circadian locomotor output cycles kaput (CLOCK) T3111C variant has been studied in association with sleep disturbances in depressed patients. The aim of this study was to investigate possible effects of T3111C CLOCK on insomnia, daytime sleepiness, sleep quality, and depression severity in a sample of 100 major depressive disorder patients. Inclusion criteria were: major depressive disorder, drug-free for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The rs1801260 single-nucleotide polymorphism (SNP) is the first human clock gene variation reported to affect human circadian rhythms (Katzenberg et al, 1998); it is a variation that occurs in the 3' untranslated region (UTR) (Robilliard et al, 2002). This SNP was associated with sleep disturbances in subjects affected by major depressive disorder or bipolar disorder ; however, Robilliard et al (2002), studying sleep patterns in normal subjects, did not find any association with rs1801260, and our team as well recently reported no associations in untreated depressed patients (Serretti et al, 2010). Besides, the rs1801260 has been studied in association with mood disorders (as a whole) (Bailer et al, 2005;Desan et al, 2000;Johansson et al, 2003) with negative results.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The rs1801260 single-nucleotide polymorphism (SNP) is the first human clock gene variation reported to affect human circadian rhythms (Katzenberg et al, 1998); it is a variation that occurs in the 3' untranslated region (UTR) (Robilliard et al, 2002). This SNP was associated with sleep disturbances in subjects affected by major depressive disorder or bipolar disorder ; however, Robilliard et al (2002), studying sleep patterns in normal subjects, did not find any association with rs1801260, and our team as well recently reported no associations in untreated depressed patients (Serretti et al, 2010). Besides, the rs1801260 has been studied in association with mood disorders (as a whole) (Bailer et al, 2005;Desan et al, 2000;Johansson et al, 2003) with negative results.…”
mentioning
confidence: 85%
“…The search was not limited by language or publication status. Additionally, we included data from our recent article (Serretti et al, 2010). Searches are available upon request from the corresponding author.…”
Section: Search Strategymentioning
confidence: 99%
“…CT have also been studied at the genetic level to determine whether clock genes are involved in the link between CT and mental disorders, but controversial results have been observed Osland et al, 2011;Serretti et al, 2010). The results from genetic studies suggest the polymorphism may not be the only factor responsible for the association between mental disorders and CT.…”
Section: Psychiatric Disorders: Clinical Implicationsmentioning
confidence: 99%
“…see 93,94,[95][96][97][98] Other studies have also investigated genes previously found to be associated with psychopathology in relation to sleep disturbances. For example, one study recently found an association between a polymorphism of the GRIA3 gene and sleep duration, which has previously been associated with depression.…”
Section: Specifying Genes and Environmentsmentioning
confidence: 99%